THE EFFECT OF JOB STRESS AND QUIET QUITTING ON TURNOVER INTENTION WITH BURNOUT AS A MEDIATION VARIABLE AMONG MOTOR SAILING VESSEL CREWS IN BONTANG CITY - Ade Bukti Ramadhan; Irsan Tricahyadinata; Irwansyah (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of job stress and quiet quitting on turnover intention with burnout as a mediating variable among Motor Sailing Vessel (MSV) crews in Bontang City, East Kalimantan. The high work pressure and changing work behaviors are critical issues in the traditional shipping sector. A quantitative approach with an explanatory design was used. The population included all active MSV crews (395 respondents) using a census technique. Data were analyzed using SEM-PLS. The results show that job stress and quiet quitting have a positive and significant effect on burnout. Burnout also has a significant positive effect on turnover intention. Furthermore, burnout fully mediates the relationship between job stress and turnover intention, as well as between quiet quitting and turnover intention. The findings indicate that psychological work conditions are key factors driving crew turnover intention. Managerial implications emphasize the importance of stress management and burnout prevention to sustain the maritime workforce.